Effects of Substituting Fishmeal (FM) Diet with a Diet of FM Plus Soy Protein Concentrate (SPC) Supplemented with Essential Amino Acids on the Growth and Gonadal Development of the Olive Flounder (Paralichthys olivaceus) - Sang Hyun Lee; Yu Jin Sim; Jong-Won Park; Minhwan Jeong; Julan Kim; Seong-Mok Jeong; Dain Lee; Hyun Chul Kim (Fishes)
Numerous studies have explored alternative protein sources to fishmeal (FM) to enhance fish diets, yet limited research exists on their effects on maturation. This study assessed the impact of replacing FM with soy protein concentrate (SPC) supplemented with lysine and methionine on growth and gonadal development in olive flounder (Paralichthys olivaceus). Three diets were tested: a control (Con) diet with 60% FM and two diets replacing FM with 25% (LF1) and 50% (LF2) SPC. Fish were fed to apparent satiation twice daily for 12 months. Growth performance and feed intake were not significantly different between groups. However, the gonadosomatic index varied with diet. Muscle composition and amino acid levels were similar across treatments, though n-3 fatty acids were higher in Con. Spermatogonia was increased, and spermatogenesis was impaired in SPC groups. At 12 months, oocytes in Con diets had absorbed yolk globules, whereas this was absent in SPC groups. Growth-related genes in the brain (growth hormones and insulin-like growth factor) were increased with higher SPC, while follicle-stimulating and luteinizing hormones decreased. Estrogen receptor α levels were elevated in SPC groups. Vitellogenin gene expression in gonads was highest in Con, while liver expression peaked in LF2. The expression of digestive enzymes, chymotrypsin2, and trypsin2 was highest in LF2, while lipase genes were lower. In summary, up to 50% FM replacement with SPC, with amino acid supplementation, supported growth performance and muscle composition without adverse effects on growth in olive flounder but influenced gonadal development.